Food habits of the exotic lizard Diploderma polygonatum polygonatum (Agamidae, Squamata, Reptilia) at a world heritage site, Yakushima Island, Japan - Satsuki Maejima; Masanao Honda; Hidetoshi Ota; Hideaki Kato; Aya Ueno; Shigenori Karasawa (Journal of Asia-Pacific Biodiversity, 2025)
This study investigated the dietary components of an exotic lizard, Diploderma polygonatum polygonatum, at the Yakushima Island World Heritage Site in southern Japan. A total of 430 individuals of various invertebrate species were found in the stomachs of 42 lizards. The most abundant order of prey animals was Hymenoptera (303 individuals in 38 lizards), followed by Coleoptera (36 individuals in 18 lizards) and Lepidoptera (24 individuals in 15 lizards). DNA barcoding was applied to 135 dietary items, and a total of 59 sequences were confirmed. BLAST searches showed that 33 of these 59 sequences presented more than 95% identity to known sequences in the database. These results showed this arboreal lizard captured invertebrates from both ground and arboreal habitats in the introduced area. Although no species on the Japanese Red List were identifiable in the stomachs of the lizards, the database of invertebrate DNA was insufficient to identify the dietary components of this predator at a World Heritage site.